A BROADBAND STUDY OF THE EMISSION FROM THE COMPOSITE SUPERNOVA REMNANT MSH 11-62 - Slane, Patrick; Hughes, John P.; Temim, Tea; Rousseau, Romain; Castro, Daniel; Foight, Dillon; Gaensler, B. M.; Funk, Stefan; Lemoine-Goumard, Marianne; Gelfand, Joseph D.; Moffett, David A.; Dodson, Richard G.; et al. (Astrophysical Journal, 2012)
MSH 11-62 (G291.0-0.1) is a composite supernova remnant for which radio and X-ray observations have identified the remnant shell as well as its central pulsar wind nebula. The observations suggest a relatively young system expanding into a low-density region. Here, we present a study of MSH 11-62 using observations with the Chandra, XMM-Newton, and Fermi observatories, along with radio observations from the Australia Telescope Compact Array. We identify a compact X-ray source that appears to be the putative pulsar that powers the nebula, and show that the X-ray spectrum of the nebula bears the signature of synchrotron losses as particles diffuse into the outer nebula. Using data from the Fermi Large Area Telescope, we identify gamma-ray emission originating from MSH 11-62. With density constraints from the new X-ray measurements of the remnant, we model the evolution of the composite system in order to constrain the properties of the underlying pulsar and the origin of the gamma-ray emission.
CRIS-Team WoS Importer:2020-01-15